MODEL REGRESI SEBAGAI PENDUGA PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP PENDAPATAN PETANI TUMPANGSARI STUDI KASUS KESATUAN PEMANGKUANHUTAN BOJONEGORO - Akub J Abdurachman (Jurnal Penelitian Hasil Hutan, 1989)
The  success  of  taungya  depends   on several  factors,   i.e.  site  quality,  social and economic   condition   of peasants.  This report  was made  as the  result  of  taungya  survey  in Bojonegoro   Forest  District,  East  Java. The influence  of several factors were  estimated    by  the  multiple   regression  equation.The  effect  of  site  quality   variable  is  significant,   and  the  effects  of  technology   and family  man power  variables are highly  significant,   but  the  levels  of  education,    labor  cost,  and peasant  location  do  not  significantly   influence  peasants' income   from   taungya.  The growth   of  basal trees area is influenced   by technology   and production   facility  cost  variables in highly  significant level.  This  occurence  showed   that  applying    "Inmas"  policy  on taungya  could  increased peasants  income,  and give positive effect   on  basal trees growth.   As  the site  quality  played  highly  significant   role on taungya  success,  it is necessary  to applydifferent   policy   to  each  location   with  different   site  quality.